2017
DOI: 10.1038/s41598-017-18291-0
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of the TRPM7 kinase domain in the early stage of amelogenesis

Abstract: Transient receptor potential melastatin-7 (TRPM7) is a bi-functional protein containing a kinase domain fused to an ion channel. TRPM7 is highly expressed in ameloblasts during tooth development. Here we show that TRPM7 kinase-inactive knock-in mutant mice (TRPM7 KR mice) exhibited small enamel volume with opaque white-colored incisors. The TRPM7 channel function of ameloblast-lineage cells from TRPM7 KR mice was normal. Interestingly, phosphorylation of intracellular molecules including Smad1/5/9, p38 and cAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…We used in situ hybridization (ISH) to verify the efficient mutagenesis of Trpm7 . In line with other studies ( 39 41 ), we observed that in control kidneys, Trpm7 was abundantly expressed in tubule segments characterized by apically located cell nuclei, a unique feature of DCT cells ( SI Appendix , Fig. S3 A ).…”
Section: Resultssupporting
confidence: 91%
“…We used in situ hybridization (ISH) to verify the efficient mutagenesis of Trpm7 . In line with other studies ( 39 41 ), we observed that in control kidneys, Trpm7 was abundantly expressed in tubule segments characterized by apically located cell nuclei, a unique feature of DCT cells ( SI Appendix , Fig. S3 A ).…”
Section: Resultssupporting
confidence: 91%
“…Although TRPM7 is essential for early embryonic development [10,163,164,165], the contribution of Mg 2+ influx through TRPM7 on the embryonic development remains controversial because TRPM7 acts as both channel and enzyme [10,164]. Several studies support the roles of kinase, which is responsible for the requirement of TRPM7 during embryogenesis [163,164,166]. The depletion of TRPM7 leads to disruption of the embryonic developments without affecting the uptake of Mg 2+ in thymocytes [164].…”
Section: Effects Of Mg2+ On the Cellular Fate And Phenotypementioning
confidence: 99%
“…These phenotypes were attributed to Mg 2+ deficiency, which was required for alkaline phosphatase activity and mineralization [21]. In addition to reduced enamel volume, another study suggested that TRPM7 was involved in the early stages of amelogenesis via cAMP response element binding protein (CREB) [23]. Therefore, both TRPM7 and CRAC components are expressed in enamel cells, and it would be of interest to understand the potential functional links between these two distinct channels.…”
Section: Introductionmentioning
confidence: 99%